CHANGES IN LIPID PEROXIDATION AND ANTIOXIDANT ACTIVITY IN PREGNANT WOMEN AND WOMEN IN LABOUR WITH DIFFUSE TOXIC GOITER - Payenok, O.S.; Payenok, A.V.; Pankiv, I.V.; Kostiv, M.O. (World of Medicine and Biology, 2019)
In order to determine the dependence of lipid peroxidation activity on the severity of thyrotoxicosis as well as its effect on antioxidant defense in the mother-placenta-fetus system, 138 pregnant women with diffuse toxic goiter were examined, 65 patients had a mild form of diffuse toxic goiter, 64 – a moderate form and 9 –a severe one. The control group consisted of 30 women with a physiological course of pregnancy. The research was carried out in the third trimester of pregnancy as well as during the process of childbirth. The concentration of the initial and final products of free radical oxidation and antioxidant defense enzymes was determined. The obtained results indicate that one of the leading causes of thyrotoxicosis is the lack of antioxidant protection of the body, the indicators of which can serve as criteria for the severity of the disease and they can be used for monitoring the onset of perinatal complications in pregnant women with diffuse toxic goiter.
Keywords: pregnancy; childbirth; peroxide oxidation of lipids; antioxidant activity; diffuse toxic goiter